2013
DOI: 10.1016/j.gpb.2013.07.004
|View full text |Cite
|
Sign up to set email alerts
|

Identification of the Phosphorylated Residues in TveIF5A by Mass Spectrometry

Abstract: The initiation factor eIF5A in Trichomonas vaginalis (TveIF5A) is previously shown to undergo hypusination, phosphorylation and glycosylation. Three different pI isoforms of TveIF5A have been reported. The most acidic isoform (pI 5.2) corresponds to the precursor TveIF5A, whereas the mature TveIF5A appears to be the most basic isoform (pI 5.5). In addition, the intermediary isoform (pI 5.3) is found only under polyamine-depleted conditions and restored with exogenous putrescine. We propose that differences in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 28 publications
1
3
0
Order By: Relevance
“…Moreover, in parasites grown in the absence of polyamines and transferred to medium with exogenous putrescine a new spot was observed that might correspond to intermediate TveIF-5A form (P2), these findings was previously observed [51]. According to previous reports, native…”
Section: Accepted Manuscriptsupporting
confidence: 61%
See 1 more Smart Citation
“…Moreover, in parasites grown in the absence of polyamines and transferred to medium with exogenous putrescine a new spot was observed that might correspond to intermediate TveIF-5A form (P2), these findings was previously observed [51]. According to previous reports, native…”
Section: Accepted Manuscriptsupporting
confidence: 61%
“…TveIF-5A is phosphorylated and O-glycosylated in the parasite [26,51], these modifications might result in an intermediate TveIF-5A isoform. These observations suggest that polyamines may play an essential role in the posttranslational modification of TveIF-5A by hypusination.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…The eukaryotic translation factor eIF5A (eIF5A1, eIF5A2, and eIF5A3 in Arabidopsis), appears to be highly conserved in all eukaryotes 69 . Interestingly, the most divergent part between plants and mammals is the N-terminus, which is conserved between plants and parasites 70 71 . The N-terminus of plant eIF5As contains a Ser residue at position 2 which we found to be more phosphorylated in snrk1α1 / α2 mutant than in Col-0 wild type ( Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Secreted tyrosine sulfated-eIF5A mediates oxidative stress-induced apoptosis by acting as a pro-apoptotic ligand [22]. It has also been reported in T. vaginalis that eIF5A is phosphorylated at serine 2 in a stretch of the consensus sequence present at the amino terminus (MSSAEEEV) [44]. A similar sequence (MSSNGSDN) is also present at the amino terminus of EheIF5A2, but not in EheIF5A1, suggesting that EheIF5A2 may be phosphorylated (Fig 2B).…”
Section: Possible Posttranslational Modifications Of E Histolytica Ei...mentioning
confidence: 67%